Budgeting Costs and Returns for Central Florida Citrus Production, 2002-03 - Ronald P. Muraro; W. C. Oswalt (EDIS)
Estimated costs and returns of growing round oranges in the Central Florida citrus area are presented for the twentieth consecutive year. Due to the freezes of the 1980's, the Central Florida citrus area refers primarily to Polk and Highlands counties. The format presented may be used by individual growers to budget costs and returns, utilizing individual data on specific groves.